Isotope ratio mass spectrometry as a tool for source inference in forensic science: A critical review. (June 2015) - Gentile, Natacha; Siegwolf, Rolf T.W.; Esseiva, Pierre; Doyle, Sean; Zollinger, Kurt; Delémont, Olivier
Abstract : Highlights: The definition of the source, often missing, prejudices results interpretation. There is a need for more fundamental data on intravariability. More studies on factors influencing the isotopic profile are essential. Abstract: Isotope ratio mass spectrometry (IRMS) has been used in numerous fields of forensic science in a source inference perspective. This review compiles the studies published on the application of isotope ratio mass spectrometry (IRMS) to the traditional fields of forensic science so far. It completes the review of Benson et al.[1] and synthesises the extent of knowledge already gathered in the following fields: illicit drugs, flammable liquids, human provenancing, microtraces, explosives and other specific materials (packaging tapes, safety matches, plastics, etc.). For each field, a discussion assesses the state of science and highlights the relevance of the information in a forensic context. Through the different discussions which mark out the review, the potential and limitations of IRMS, as well as the needs and challenges of future studies are emphasized. The paper elicits the various dimensions of the source which can be obtained from the isotope information and demonstrates the transversal nature of IRMS as a tool for source inference.